Material Behaviour of Three Blade Propeller Using Metal Additive Manufacturing Techniques - Avinash Malladi; K. Karunakaran; R. Saravanan; Yalew Asres (Advances in Materials Science and Engineering, 2022)
The defects stored during the fusion of the laser with the metal powder bed determine the optimal performance of fatigue and lifelong disintegration of the formed metal components. The advantage of using recent technologies of prototyping is very much powerful in understanding the physical process. The current works provide the details of the same for a 3-blade propeller with its thermomechanical approach to identified parameters. The results provide the materials used and their behaviour with the parameters which conclude in prescribing the material for the various applications. The investigation aimed to optimize the position of the object (3-blade Propeller) and material for printing through simulation before it was printed. The material choices of aluminium AlSi10 Mg, stainless steel 17–4 and stainless steel 316L were considered. The ten different object positions were considered and ranked by the minimum support area required. The top and bottom-ranked positions were further investigated with three different materials, namely Aluminium AlSi10 Mg, atainless steel 17–4, and stainless steel 316L, in which the Rank 1 position, the material of Aluminium AlSi10 Mg exhibits the minimum of maximum displacement (2.348e-01 mm), plastic strain (0.05), and the Von Mises Stress (2.086e+02 MPa).